Civics beyond critics character education in a liberal democracy - MacMullen, Ian 1976- (Oxford political theory, 2015)
Examines the orthodox view that education for civic character must be limited to avoid compromising its recipients' ability to think and act as critically autonomous citizens, arguing that traits such as law-abidingness, civic identification, and support for society's institutions are equally essential.